Intensity, Profitability and Disclosure of Biological Assets of Agricultural Companies - Nikmah Nikmah; Muhammad Taufik; Fitrawati Ilyas (Jurnal Akuntansi, 2022)
The agricultural sector is a sector that plays an important role ini the Indonesian economy because Indonesia is an agriculture country. In agriculture companies, biological asset are part of the company’s assets. This study examines the effect of biological asset intensity and profitability on the disclosure of biological assets of agriculture companies. This study was tested using multiple regression analysis. The sample used in this study is agricultural companies listed on the Indonesia Stock Exchange in 2018-2020. The data in this study is obtained from secondary source i.e. www.idx.com. The results of this study show the intensity of biological assets has a positive effect on the disclosure of biological assets and profitability does not have a positive effect on the disclosure of biological assets.